?A MECHANISM FOR NITRIC ACID INDUCED OXIDATION PRODUCTS OF YOHIMBANE ALKALOIDS (Biological Sciences - PJSIR, 1995)
The oxidation of two yohimbane alkaloids(reserpineand rescinnamine) by nitric acid has been studied [1,2]and mechanisms arenowproposedfortheoxidationproducts.Theoxidationpatternofthesealkaloidsappeartobethesame invariousorganicsolventsandtheratemaybeinfluenceddependinguponthesolventcharacteristics,i.e.dielectriccon- stant, dissociation constant and viscosityof the medium in therange studied.